Variations in bile tolerance among Lactococcus lactis strains derived from different sources - Takanashi, Shihori; Miura, Ai; Abe, Koko; Uchida, Junya; Itoi, Shiro; Sugita, Haruo (Folia microbiologica, 2014)
Lactococcus lactis subsp. lactis has been isolated from the intestines of marine fish and is a candidate probiotic for aquaculture. In order to use the bacterium as a probiotic, properties such as bile tolerance need to be assessed. Here, we compared bile tolerance in L. lactis strains derived from different sources. Three L. lactis subsp. lactis strains from marine fish (MFL), freshwater fish (FFL), and cheese starter (CSL) were used along with an Lactococcus lactis subsp. cremoris strain from cheese starter (CSC). The four strains were grown under various culture conditions: deMan-Rogosa-Sharpe (MRS) broth containing bile salts/acids, MRS agar containing oxgall, and phosphate-buffered saline (PBS) containing fish bile. Survival/growth of the strains in the presence of sodium cholate and sodium deoxycholate varied in the order MFL, CSL > CSC > FFL; in the presence of sodium taurocholate, the order was MFL > CSL > CSC > FFL. In liquid media containing various concentrations of oxgall, survival of the strains was observed in the order MFL > CSL > FFL and CSC. The survival of MFL was not affected by bile collected from the goldfish (Carassius auratus subsp. auratus) or the puffer fish (Takifugu niphobles), although the other strains showed significant inhibition of growth. It is a novel and beneficial finding that MFL has the highest resistance to bile acid.
Keywords: Aquaculture; Colony Count, Microbial; Fishes; zvířata; ryby; počet mikrobiálních kolonií; Lactococcus lactis; probiotika; Bile Acids and Salts; vodní hospodářství; žlučové kyseliny a soli; Probiotics; Animals